“SANJHYA” THE GODDESS TRADITIONAL ART FORM OF INDIAN ART - Vikrant, Dr.Vikrant Shah (International Journal of Research -GRANTHAALAYAH, 2021)
If there is any priority for mankind with bread, cloth and house then it will be said to be an expression of his art, his feelings. This is the reason why pre-historic man has also painted on the walls of caves, which today help historians to understand that ancient civilization are the center of interest of tourists. "Sanjhya" is a very ancient and the goddess traditional art form of Indian. Perhaps it is a spiritual image to connect the divine to the earth. Apart from Madhya Pradesh, "Sanjhya" is spread in the terrain of Punjab, Rajasthan, Uttar Pradesh, and Haryana etc. Most of the women and youth are making Sanjhya in specific art form. The specialty of these folk art is that these are three-dimensional art on wall consider it to be a reflection of simplicity and culture of ordinary living being through his arts. These artworks show how colorful the imagination of a human can make even a simple straight life. Animals such as peacocks, lions, bears, deer, crocodiles, fish, rivers, mountains, fields, trees, moon are the subjects of their art work, which these community give a multi-colored look on a wall of length and width. These artwork made from unique images of human and divine also. Sanjhya is used on the entrance of the house and on the walls in the courtyard and portrays the family wedding, death or other religious occasions. These pictures are a simple demonstration of the nature and living conditions of these people.